An innovative strategy on co-production of porous carbon and high purity hydrogen by alkaline thermal treatment of rice husk. (30th June 2022) - Qi, Penggang; Su, Yinhai; Zhang, Shuping; Jiang, Mei; Sun, Xiaofei; Shi, Lei; Xiong, Yuanquan
Abstract: An innovative biomass conversion method was proposed to co-produce porous carbon and high purity hydrogen by alkaline thermal treatment (ATT). Hydrogen with purity over 80 vol % and porous carbon with a specific surface area of 2298.5 m 2 /g were co-produced at 500 °C for the first time. In this study, the effects of various reaction parameters on hydrogen production and the properties of porous carbon were investigated. The composition of gas products was tested, and the pore structure, morphology, graphitization degree and crystal structure of porous carbon were analyzed. The results showed that the optimum experimental conditions were alkali/rice husk mass ratio of 3:1, reaction temperature of 500 °C and reaction time of 60 min. A variety of characterization results showed that alkali etched the surface of rice husk at appropriate temperature, forming a large number of pore structures, and releasing volatile substances and hydrogen. The addition of alkali reduced the microcrystalline structure between graphite layers and increased the proportion of amorphous structure in porous carbon. Electrochemical test results showed that the specific capacitance of porous carbon prepared under the best reaction conditions reached 228.94 F/g at the current density of 0.2 A/g. Graphical abstract: Image 1 Highlights: Porous carbon and hydrogen were co-produced by alkaline thermal treatment. Hydrogen with yield of 1018.13 mL/g was obtained by alkaline thermal treatment. The porous carbon with a specific surface area of 2298.5 m 2 /g was obtained at 500 °C. The mechanism of alkaline thermal treatment was studied. The specific capacitance of porous carbon reached 228.94 F/g at 0.2 A/g current density.